Pembuatan Bibliografi Beranotasi Untuk Subyek Kedokteran Menggunakan Microsoft Access di Perpustakaan Kopertis Wilayah X - Ismiatul, Yolanda; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
This paper contains an annotated bibliography by subject manufacture medicine using the Microsoft Access at Libraries Kopertis Region X. This study aimed to describe the process of making medical subjects annotated bibliography using Microsoft Access 2007 in the Library Kopertis Region X Padang. Data were collected through observation and direct observation in the Library Kopertis Region X. Analyzing the data be descriptive. Based on data analysis, creation of bibliographic summarized as. (1) Specifies the title of the bibliography is based on information requested by library visitors, (2) collection reading materials by direct collection, (3) selection reading materials with form of monographs, (4) classification grouped based DDC. (5) typing the manuscript bibliography can be helped using Microsoft Access program, (6) index creation can use Microsoft Access program, (7) create keywords create by using the language of the medical dictionary, and (8) checks script.